Religion as a Resource? The Impact of Religiosity on the Sense of Purpose in Life of Young Muslim Refugees in Germany - Engel, Daniel; Penthin, Marcus; Pirner, Manfred L.; Riegel, Ulrich (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2024)
This study examines the relationship between religiosity and purpose in life among young Muslim refugees (n = 222; Mage = 20.18 years) in Germany, a topic little explored to date. Consistent with previous research, respondents felt a moderate but positive sense of purpose in life, which was fostered by religiosity. Regression analysis demonstrated that even after controlling for physical health and social support, religiosity remained a substantial predictor of purpose in life; its effect size did not differ significantly from the other two variables in the model. The findings emphasize the importance of religiosity and social support for young Muslim refugees’ well-being.